2008
DOI: 10.1007/s00256-008-0457-0
|View full text |Cite
|
Sign up to set email alerts
|

Articular nodular fasciitis in the glenohumeral joint

Abstract: We describe a case of multiple intra-articular masses in the glenohumeral joint of a 15-year-old patient. The patient was treated with arthroscopic excision of the masses and synovectomy. Histological and immunohistochemical studies were consistent with those of a nodular fasciitis. Follow-up examination did not reveal recurrence at 6 months. In this article we report the first case of articular nodular fasciitis in the glenohumeral joint with unusual imaging findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…During the preoperative follow-up period, the patient underwent sequential MRI studies and no enlargement of the mass was demonstrated. These clinical findings are consistent with the characteristic features of intra-articular nodular fasciitis previously reported [2][3][4][5][6][7].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…During the preoperative follow-up period, the patient underwent sequential MRI studies and no enlargement of the mass was demonstrated. These clinical findings are consistent with the characteristic features of intra-articular nodular fasciitis previously reported [2][3][4][5][6][7].…”
Section: Discussionsupporting
confidence: 92%
“…The prognosis of the condition is excellent and local recurrence of the lesion has never been seen among previously reported cases [2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although information on imaging studies for intra-articular nodular fasciitis is limited, the current case showed nonspecific findings on MRI images, with homogeneous iso to low signal intensity on T1-weighted images and a heterogeneous, low to high signal intensity on T2-weighted images as reported previously (3)(4)(5)(6)(7). In this present case, conventional MRI with no contrast study showed nonspecific signal intensity of the lesion similar to previous reports, resulting in difficulty in making a precise pre-operative diagnosis on MRI.…”
Section: Index Termsmentioning
confidence: 77%